JavaServer faces live lessons - Geary, David M. 1957- (Prentice Hall, 2012)
"This engaging video by the co-author of the bestselling Core JavaServer Faces, provides expert guidance on building robust applications with minimal hand coding and maximum productivity--without requiring any knowledge of servlets or other low-level plumbing. It provides a complete explanation of the basic building blocks--from using standard JSF tags, to working with data tables, and converting and validating input, as well as coverage of advanced tasks, such as event handling, extending the JSF framework, and connecting to external services. Each lesson includes solutions to a variety of common challenges, as well as notes on debugging and troubleshooting."--Resource description page.
Title from title screen
Keywords: JavaServer pages; Web site development; Web sites -- Design; Sites Web; Développement; Sites Web; Conception; Web sites; Design